The activity of Bacillus thuringiensis Vectobac G on the biochemical compositions of Culex pipiens and Culiseta longiareolata (Diptera: Culicidae) mosquito larvae - Bouaziz, A; Aissaoui, L; Boudjelida, H. (Eco. Env. & Cons, 2022)
Culex pipiens and Culiseta longiareolata, are domestic mosquitoes, and ones of the most dominant and abundant mosquito species in the urban areas of Algeria. Thus, the present study was conducted to evaluate the larvicidal activity of Bacillus thuringiensis (Bt.) Vectobac G and to estimate the disturbance of main body metabolites in the tissues of fourth instar larvae of Cx. pipines and Cs. longiareolata. The toxicological essays were done using different concentration of Bti vectobac G against a new exuviated fourth instar larve of Cx. pipiens, and Cs. longiareolata for 24h of exposure time. The results showed a toxic effect with a concentration-response relationship of this product. The biochemical analyses were carried out with the estimated lethal concentrations of both used species (Cx. pipiens: LC50=0.81 g /l and LC90=3.57 g /l; Cs. longiareolata: LC50=1.80 g/l and LC90=5.43 g/l) on the fourth instar larvae. As a result, Bti. Vectobac G caused a significant decrease in the whole body weight in the treated larvae as compared to the control series. Moreover, biochemical analyses revealed an increase in carbohydrates levels, and a decrease in protein and lipids in the whole larvae body treated with the lethal concentrations as compared to the control series for the both species Cx. pipiens and Cs. longiareolata.